Makna Simbolik Tari Pabitte Passapu Pada Upacara Pernikahan di Kecamatan Kajang - Rahma M (Seminar Nasional LP2M UNM, 2019)
The meaning of dance movements certainly cannot be equated with the meaning of a word or language in which almost all words can be explained as meaning in the motion contained in a dictionary, although there are several forms of motion art that can be interpreted every movement made for example pantomime, but the motion in dance is not because the meaning contained therein is usually related to the philosophy or philosophy of life of a society or for certain needs. Like the people of South Sulawesi, which consists of hundreds of tribes and ethnicities, of course, have different cultural and artistic forms and are full of meaning that is directly related to the lives of the people. One of them is Pabitte Passapu Dance at a wedding ceremony in the Kajang sub-district community in Bulukumba Regency.